Diltiazem-tetraiodide bismuthate (III) based PVC membrane for selective determination of diltiazem hydrochloride - Kassab, Ryad; Aboudan, Mahmoud (JOURNAL OF ADVANCES IN CHEMISTRY, 2023)
A new coated-wire electrode based on PVC membrane plasticized with dioctyl phthalate (DOP) and containing the diltiazem-tetraiodido bismuthate (III) ion association coated on a silver wire was constructed and used for potentiometric determination of diltiazem hydrochloride. The electrode performance was characterized and optimized according to the following experimental criteria: membrane composition, soaking time, working pH range, and response time. The interference caused by different species was investigated as well. The best membrane composition was found to be 49.75% of PVC and DOP, 0.5% ion pair. This sensor showed a linear response with a good Nernstian slope of 57.60±1.38 mV/decade over the concentration range 5.0×10-5 – 2.50×10-2 M, the detection limit was 2.88×10-5 M, and it was usable within a wide pH range of 2.5–8.0. The electrode showed a fast response time (18 sec), with a relative long lifetime (2.4 months, 2 h a day). The isothermal coefficient (dE°/dT) of the electrode was calculated and found to be 5.36×10-4 V/℃ within 20 – 80℃, which exhibits a good thermal stability. The coted-wire electrode was successfully applied for the potentiometric determination of diltiazem hydrochloride both in pure form and pharmaceutical preparations. The dissolution test of the drug was carried out as well.